Causes of the Stops: Selected Examples from Tafsir al-Qurtubi "Al-Jāmi' li Ahkām al-Qur'ān" | علل الوقوف: شواهد منتقاة من تفسير القرطبي الجامع لأحكام القرآن - Mhamed Rebba (Al-Zahra : Journal for Islamic and Arabic Studies, 2021)
The study of the causes of the Qur’anic endowment in the Book of God Almighty is a topic of great importance and ignorance of which cannot be tolerated at all, and for this reason the ancient linguists and scholars of the Qur’anic sciences took care of it and used it in their syntheses and consulted with it a lot. It is the result of being influenced by a number of different sciences. Hence this paper came to shed light on the reasons calling for the differences of endowment scholars as well as the commentators about determining the places of endowment and beginning in the verses of the Noble Qur’an, and that their endowments and beginnings were based on a set of rules: explanatory, grammatical, reading, and jurisprudence. The importance of stopping and starting in understanding the meanings of the Qur’an correctly. The search for the reasons that motivate the different aspects of endowment and initiation: in terms of grammar, jurisprudence, and doctrine. My interest in the interpretation of Al-Qurtubi: "The Collector of the Laws of the Qur'an", as I found it a useful book and an original source in a number of sciences. As for the method used in dealing with the subject of the research, it is the inductive-analytical method. One of the advantages of my research, as I see it, is that I have never had a similar study in revealing the reasons for standing and beginnings through the interpretation of al-Qurtubi, and my study was unique in linking the reasons for disagreement with Quranic models of the interpretation referred to previously. In addition to the need for the reader and the exegete to pay attention to understanding the science of endowment and the beginning, its causes, and its aspects... so that he can differentiate between the different meanings and the two different rulings.